The principle of the best interest of the child in the convention of the rights of the child and in the Polish Law (selected problems) - Mendecka, Karolina (Acta Universitatis Lodziensis. Folia Iuridica, 2016)
Children’s rights are one of the most important and challenging international and national regulations. The Convention on the Rights of the Child as well as the Polish law explicitly stipulate that the best interest of the child has to be taken as primary consideration. The scope of this principle is defined mainly by the judicatory and the doctrine. The best interest of the child principle is not only primary, but should be superior to other interests and principles. Where a conflict of interests arises, the child’s best interest should always be a priority. This article elaborates on the condition of children’s rights in Poland, with particular reference to the best interest of the child principle in the light of the Convention on the Rights of the Child and of the Polish legal system.